Desenvolvimento de base tecnológica: gestão e georreferenciamento da cadeia produtiva da erva-mate no estado do Rio Grande do Sul - Pires, Fábio Soares (2016)
This study aimed to develop three computer systems, modeled to look for information that describes the current context of the production chain of Yerba Mate in the state of Rio Grande do Sul. Meetings were held with members of ervateiro sector to prospect all the information that pervade agricultural activities involved. So with this data, it was possible to organize the structure of the proposed systems to make the collection of data regarding the properties, superior trees, nurseries, ervateiras and factories. As a result they have developed the C7-Ilex, the GeoMate_RS and a web system. Both with the registering functions georeferenced data and viewing possibility on maps. But the GeoMate_RS will be responsible for assisting in information management through reporting, graphics and images. This proposal was presented at the Second Production Chain Sustainability State Congress of Yerba Mate, which occurred along the TURISMATE 2015. Due to the impact, on June 16, 2016 was signed SEAPI 154_2016 ordinance that officiated the Electronic Operating System for Register Ervateiro in the state of Rio Grande do Sul. Thus, it is expected that these systems specifically used to generate information, help the IBRAMATE in making strategic actions and policies for the development of the productive chain, and also contribute to a reduction many challenges faced on the economic environment in which it is the country.